Review Article - Cardiomyopathy Associated With Targeted Therapy for Breast Cancer. (February 2016) - Sivagnanam, Kamesh; Rahman, Zia U.; Paul, Timir
ABSTRACT : Background: : Chemotherapeutic agents directed against human epidermal growth factor receptor 2 (HER‐2) have significantly improved the prognosis of patients who are positive for this receptor. However, cardiomyopathy remains as a common adverse effect of using these agents. Materials and Methods: : Literature search was conducted via PubMed using the keywords of "Trastuzumab Cardiomyopathy, " "Lapatinib Cardiomyopathy" and "Pertuzumab Cardiomyopathy, " which provided 104 results. These articles were then screened for relevance to the targeted subject based on their title and abstracts. Case reports and articles that were not discussing any aspect of cardiomyopathy secondary to targeted therapy for breast cancer and articles not in English were eliminated. After elimination, a bibliography search among selected articles was done and a total of 46 articles were identified. The collected articles were then meticulously analyzed and summarized. Results: : The use of human epidermal growth factor receptor 2 (HER‐2) receptor targeted chemotherapy in breast cancer is limited because of a higher incidence (19–22%) of cardiomyopathy. The incidence of cardiomyopathy is not dose dependent and in most cases it is reversible after discontinuation of the drug and treatment with heart failure medications. Severe adverse outcomes including death or permanent disability are rare. Conclusion: : HER‐2 targeted chemotherapy for breast cancer has a higher incidence of associated reversible cardiomyopathy. Patients should be monitored by serial echocardiography starting at the beginning of the treatment and followed by every 3 months until the completion of chemotherapy. Co‐ordination between oncologists and cardiologists is needed to develop evidence‐based protocols to prevent, identify, monitor and treat trastuzumab‐induced cardiomyopathy.